Tinjauan Kinerja Perusahaan, Konservatisme Akuntansi dan Kualitas Laba - Salma Faisha Nanda; Ade Imam Muslim (Department of Accounting, Faculty of Economics & Business, 2022)
This study aims to determine the influence of earning growth and accounting conservatism of earning quality in companies listed on the Indonesian Stock Exchange (IDX) in 2015-2020. In this research, we obtained data from the company’s financial statements with 300 firm years observation in the food and beverage sector, cigarette industry manufacturing companies, property and real estate sector companies, as well as airline sector companies listed on the Indonesian Stock Exchange (IDX), then analyzed using Panel Data Regression Analysis and the hypothesis were tested using Eviews. Our studi provide evidence that earnings growth and accounting conservatism had a significant effect on the quality of company earnings.